Tetrahydroxyphthalocyanine as a potential nonlinear optical material - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (My University, 2023)
© 2022We have synthesized a new zinc(II)-phthalocyanine (ZnPc) incorporating hydroxyl groups at the peripheral positions. This new zinc(II)-tetra-hydroxyphthalocyanine (1) has been characterized by high-resolution MALDI TOF MS, UV-Vis, FT-IR (ATR), and 1H- and 13C-NMR techniques, and further by the electrochemical measurements. DFT and TD-DFT computations were performed to model plausible structure and also analyze the electronic structure and optical properties of 1. The effects of the polarity and hydrogen bonding ability of the hydroxyl substituents on the peripheral positions of 1 on the optical and electrochemical properties are reported in this study. The redox behavior of 1 in dimethyl sulfoxide (DMSO) was determined by voltammetry and colorimetry supported in situ spectroelectrochemistry. The nonlinear absorption and optical limiting (OL) properties of 1 were measured in tetrahydrofuran (THF) by utilizing the open aperture Z-scan technique with nanosecond pulses at 532 nm. The sample demonstrated good reverse saturable absorption and OL behaviors. The ultrafast pump-probe experiments revealed the intersystem crossing (ISC) mechanism (triplet-triplet transition) and the nonlinear absorption mechanism of the compound. The results indicate that this new phthalocyanine (1) can be considered a potential candidate for low-power OL applications.
Keywords: Kimya; Analitik Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Chemistry; Analytical Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; KİMYA, ANALİTİK; SPEKTROSKOPİ; KİMYA, ORGANİK; Natural Sciences (SCI); CHEMISTRY; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; CHEMISTRY, ORGANIC; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Physical Sciences; Organic Chemistry; Zinc; Phthalocyanine; DFT; Nonlinear; Electrochemistry; ZINC-PHTHALOCYANINE; LIMITING PROPERTIES; PHOTOPHYSICAL PROPERTIES; FREE-BASE; EXCHANGE; BEHAVIOR